2012
DOI: 10.1371/journal.pone.0047443
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Brain Stress Testing: BOLD Magnetic Resonance Imaging with Computer-Controlled Delivery of Carbon Dioxide

Abstract: BackgroundAn impaired vascular response in the brain regionally may indicate reduced vascular reserve and vulnerability to ischemic injury. Changing the carbon dioxide (CO2) tension in arterial blood is commonly used as a cerebral vasoactive stimulus to assess the cerebral vascular response, changing cerebral blood flow (CBF) by up to 5–11 percent/mmHg in normal adults. Here we describe two approaches to generating the CO2 challenge using a computer-controlled gas blender to administer: i) a square wave change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…The simple on-off "square wave" CO 2 stimulus is straightforward to apply and a robust probe for CVR dynamics (Mutch et al, 2012). Our results show that a simple nasal cannula is sufficient to induce significant whole-brain BOLD response under CO 2 challenge with acceptable acquisition time, and the setup necessary for the CO 2 clinical protocol does not interfere with the structural MRI typically performed in routine workup on cognitive decline.…”
Section: Cvr Dynamics Assessment In Clinical Practicementioning
confidence: 82%
See 1 more Smart Citation
“…The simple on-off "square wave" CO 2 stimulus is straightforward to apply and a robust probe for CVR dynamics (Mutch et al, 2012). Our results show that a simple nasal cannula is sufficient to induce significant whole-brain BOLD response under CO 2 challenge with acceptable acquisition time, and the setup necessary for the CO 2 clinical protocol does not interfere with the structural MRI typically performed in routine workup on cognitive decline.…”
Section: Cvr Dynamics Assessment In Clinical Practicementioning
confidence: 82%
“…The application of carbon dioxide (CO 2 ) induces vasodilation, which can be assessed in the entire brain parenchyma using blood oxygen leveledependent (BOLD) MRI (Cohen et al, 2002;Haller et al, 2006Haller et al, , 2008Kassner and Roberts, 2004;Mutch et al, 2012;Ziyeh et al, 2005). Beyond changes in CVR amplitude, 1 previous functional magnetic resonance imaging (fMRI) study (Cantin et al, 2011) observed that a different slope of response to hypercapnia was found in MCI and AD patients than in control subjects, suggesting that the temporal dynamics of CVR may differ.…”
Section: Introductionmentioning
confidence: 99%
“…6 Improvements of BOLD CVR methodologies have been proposed [13,15] and may increase sensitivity and quantification of (regional) CVR measurements in subjects with high-grade cerebral glioma.…”
Section: Limitations and Future Considerationsmentioning
confidence: 99%
“…CO 2 is a potent vasodilator, triggering changes in vascular tone through the arterial baroflex. PETCO 2 changes can be induced through manually adjusted administration of blended gases (Bandettini and Wong, 1997 ;Cohen et al, 2004;Yezhuvath et al, 2009), end-tidal forcing (Poulin et al, 1996) or more recently, computerized PETCO 2 targeting (Conklin et al, 2011;Han et al, 2011;Mandell et al, 2011;Mandell et al, 2008;Mark et al, 2010;Mikulis et al, 1989;Mutch et al, 2012;Prisman et al, 2008;Slessarev et al, 2007;Spano et al, 2013;Vesely et al, 2001). The latter method provides immediate and robust PETCO 2 changes, and we have used it extensively in our own work (Chen and Pike, 2010a;Chen and Pike, 2010b;Halani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%